Penerapan Motif Flora dan Fauna sebagai Inspirasi Penciptaan Karya Batik Tulis - Eka Fitria Ningsih; Misgiya Misgiya (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
Batik has been recognized by UNESCO as a Masterpiece of the Oral and Intangible Heritage og Humanity on October 2, 2009. Hand-drawn batik is batik produced using a canting tulis as a tool to apply wax to the surface of the cloth. In creating this work, the author used the Hendriyana creation method. The stages of the process of creating a work of art from this method include: 1. Preparation stage 2. Imagination stage 3. Imagination development stage and 4. Work stage. This creation research aims to produce innovations in flora and fauna works in hand-drawn batik motifs. The flora and fauna motifs that the author uses in creating this hand-drawn batik work are rose, dahlia, and butterfly motifs. The results of the creation of hand-drawn batik works with flora and fauna motifs produced 12 batik works in the form of two-dimensional works measuring 100 x 200 cm which can be used as clothing materials. Using the colet technique in the coloring process to produce more dynamic and expressive color variations. The process of creating hand-drawn batik begins with the process of making a motif on paper, transferring the pattern from the paper to the cloth, the canting process, giving color to the cloth, and drooping the cloth.